Lung donation after cardiac arrest. Challenges and opportunities. Literature review - I. V. Pashkov; M. G. Minina; N. V. Grudinin; V. K. Bogdanov (Вестник трансплантологии и искусственных органов)
The global development of transplantology faces several objective obstacles. One of the major ones is widespread organ shortage. This is most pronounced in clinical lung transplantation (LT). The development of this area is directly connected with more intensive development of available donor resources and search for new sources of donor organs that are suitable for transplantation. Along with the existing methods of increasing the number of lungs suitable for transplantation, LT with donation after cardiac death (DCD) is attracting increasing attention. The effectiveness of this approach has been confirmed by the International Society for Heart and Lung Transplantation and deserves more attention from Russian specialists.